Medical informatics: textbook - Омельченко, В. П. физика 19480429 Виталий Петрович (Textbook, 2020)
This textbook outlines the main issues of medical informatics. Information on modern technologies used in medicine and health care is given. The principles of storage, retrieval, processing and effective use of medical information, data and knowledge to solve problems and make decisions using computer technology are described. The content of the textbook complies with the new federal state educational standards for the study of the discipline "Medical Informatics" in medical universities at the Medical and Preventive Faculty, Paediatric, Pharmaceutical, Dental Faculties as well as the subject ?Informatics. Medical Informatics. Statistics? at the public health faculty.